PRODUKSI INULINASE OLEH KHAMIR Pichia manshurica DUCC Y-015 PADA TEPUNG UMBI DAHLIA (Dahlia variabilis Willd.) DENGAN VARIASI KONSENTRASI MnSO4.H2O DAN WAKTU INKUBASI - Berlian Abadianti; Agung Suprihadi; w wijanarka (Jurnal Akademika Biologi, 2017)
Inulinase (E.C. 3.2.1.7) is an enzyme which able to hydrolyze an inulin into fructose and fructooligosaccharides.  The main application of inulinase enzyme in the food industries is as the ingredient in producing High Fructose Syrup (HFS). Moreover, the other important applications of inulinase enzyme are to produce ethanol, inulooligosacarida (IOS), fruktooligosacarida (FOS), pullulan, sorbitol, etc.  Pichia manshurica DUCC Y-015 is kind of yeast that is capable in producing inulinase in medium containing inulin. Optimization of inulinase enzyme production needs to be done to increase inulinase production, the way that could be conducted is by the addition of metal ion and optimization of incubation time. The purpose of this research is to investigate the effect of adding mangan ion (MnSO4.H2O) and incubation time. In conducting this study, the researcher applies experimentally research by using Randomized Complete Block Design (RCBD) factorial pattern. The first factor is concentration of MnSO4.H2O, with concentration level 0 mM (M0), 0,1 mM (M1), 0,5 mM (M2). The second factor is the variation of incubation time, i.e. 6 hours (I6), 12 hours (I12), and 18 hours (I18) with three times repetition. The collected data were analyzed using ANOVA 5% signification (α= 0,05) and completed by the Duncan test. The result of analysis shows that variation of MnSO4.H2O concentration and incubation time does not significantly influential on inulinase activity of Pichia manshurica DUCC Y-015.Keywords: Inulinase, Inulin, Pichia manshurica DUCC Y-015, MnSO4.H2O, Incubation time.